A density-controlled scaffolding strategy for covalent functionalization of carbon-fiber microelectrodes1. Issue 17 (7th September 2015) - Yang, Yuanyuan; Ibrahim, Ahmad A.; Stockdill, Jennifer L.; Hashemi, Parastoo
<x xml:space="preserve">Abstract</x> We describe a covalent functionalization method for creating density-controlled selective adsorption sites on carbon-fiber microelectrodes.